Correlation between body condition score with estrus and reproductive performance in dairy cow post ovary hypofunction - Aqil Adyatama; Anis Muktiani; Daud Samsudewa (Universitas Sebelas Maret, 2024)
Objective: The objective of this research is to determine the relationship between body condition score (BCS) with estrus performance and reproductive performance in dairy cow post ovary hypofunction.Methods: Observational method by collecting primary and secondary data were used in this research. Primary data includes BCS and estrus performance. Secondary data includes reproductive performance. Purposive sampling method with criteria minimum parity 1 were used. Correlation and simple linear regression were used to analyze the data.Results: The results showed moderate correlation coefficient and regression equation of BCS with redness of vulva (0.531 and Y = 1.389+0.958 X), behavior changing (0.597 and Y = 0.75+0.896 X), mucus cervix intensity (0.503 and Y = 0.889+1.583 X), uterine erection (0.597 and Y = 1.500+1.792 X), service per conception (0.459 and Y = 4.33–1.09 X), estrus post-partum (0.594 and Y= 202.3–38.831 X) and days open (0.498 and Y= 217.271–40.832 X).Conclusions: The conclusion of this research is dairy cow with minimum BCS 3 is needed during mating post ovary hypofunction.